Comparison of positive detection rates between fluorescent staining and traditional KOH wet mount methods in the diagnosis of superficial fungal skin infections and analysis of factors associated with missed diagnosis - Li Zhou; Lihua Hu; Lu Pan; Feng Lin; Jia Huang; Yifan Tao; Mingqin Lu; Bo Yang; Dan Li (Frontiers in Medicine, 2026)
Background Superficial fungal skin infections represent one of the most prevalent dermatological conditions worldwide, necessitating accurate and rapid laboratory diagnosis for appropriate therapeutic management. Objective This retrospective study aimed to compare the positive detection rates between fluorescent staining and traditional KOH wet mount methods in patients with clinically suspected superficial fungal infections and to identify factors associated with missed diagnosis. Methods A total of 151 patients with clinically suspected superficial fungal skin infections presenting to our dermatology department between January 1, 2025, and June 30, 2025, were enrolled. All specimens underwent parallel examination using both fluorescent staining (calcofluor white) and traditional 10% KOH wet mount methods. Diagnostic performance parameters including sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Multivariate logistic regression analysis was performed to identify independent risk factors for missed diagnosis. Results The fluorescent staining method demonstrated a significantly higher positive detection rate (78.81%, 119/151) compared to the KOH wet mount method (58.28%, 88/151) (χ 2 = 15.73, P < 0.001). Using fungal culture as the gold standard, fluorescent staining achieved a sensitivity of 94.35% versus 73.39% for KOH ( P < 0.01), with specificities of 91.67 and 95.83%, respectively. Multivariate analysis revealed that prior antifungal treatment (OR = 3.84, 95% CI: 1.62–9.11, P = 0.002), inadequate specimen collection (OR = 2.76, 95% CI: 1.18–6.45, P = 0.019), and nail specimen type (OR = 2.31, 95% CI: 1.04–5.13, P = 0.039) were independent risk factors for missed diagnosis with KOH wet mount examination. Conclusion Fluorescent staining provides superior diagnostic performance compared to traditional KOH wet mount for superficial fungal infections, with significantly higher sensitivity and comparable specificity.